Trust and authority in the periphery of world scholarly communication: A Malaysian focus group study - A., Abrizah; Badawi, Fathiah; Zoohorian-Fooladi, Niusha; Nicholas, David; R. Jamali, Hamid; A. K., Norliya (Malaysian Journal of Library and Information Science, 2017)
The paper provides the results of the first phase of the research project Trust and Authority in Scholarly Communications: The Periphery of World Scholarship in the Digital Era conducted in Malaysia. The objective of the study is to examine the changing behaviours and attitudes of academic researchers in today’s scholarly digital environment, with respect to how they determine authority and trustworthiness in the sources they use, cite, and publish in. This phase utilised focus groups to address the research objective. Five focus groups were held during the period of December 2013 to April 2014 in three universities in Kuala Lumpur. In all a total of 48 researchers attended the focus groups, comprising 21 scientists and 27 social scientists. Findings indicate that peer-reviewed journals are still the central to the authors, however they seem to have more freedom in relation to journals they read and cite, compared to publish. Overall, authors view that scholarly resources that are current, relevant, authored by credential scholars, peer-reviewed, having credible reference lists, published by reputable journals, and having online presence are fit for scholarly utilisation. The extent to which authors are prepared to believe that the scholarly information source and channel are trustworthy for publication rely on it in view of its impact, indexation status, reputation, peers’ recommendation, accessibility and visibility, and authority’s approval. New forms of communication channels such as social media or new journal models are not much used in formal scholarly communication. The focus groups provided the direction for questionnaires and interviews that would follow.The paper also discusses the implication of the findings to academic librarians towards delivering the right services to meet the needs of the scholarly community.